2021
DOI: 10.1002/aenm.202003405
|View full text |Cite
|
Sign up to set email alerts
|

A Commercial Benchmark: Light‐Soaking Free, Fully Scalable, Large‐Area Organic Solar Cells for Low‐Light Applications

Abstract: Low‐light applications provide an exciting market opportunity for organic solar cells (OSCs). However, so far, studies have only considered OSCs of limited commercial viability. Herein, the applicability of a fully‐scalable, flexible, inverted non‐fullerene acceptor (NFA) containing OSC is demonstrated by showing its superior performance to silicon under low‐light, achieving 40 µW cm−2 maximum power output at 1300 lx illumination. The effect of parasitic resistance and dark current on low‐light performance are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 58 publications
(81 reference statements)
2
54
0
Order By: Relevance
“…Recently, Luke et al investigated the low light IOPVs device performance of commercially feasible inverted device architecture, employing all solution processed R2R fabrication technique and relatively low-cost polymer (P3HT) donor and NFA (O-IDTBR) acceptor as active layer materials. [104] This is particularly important as thick layers are easier to manufacture by R2R processes (Figure 9a). Their results suggested that screening of possible low light OPV devices using 1 sun illumination is not appropriate, as some OPV devices that perform well at low light intensities may appear to not work well under standard illumination conditions.…”
Section: Large-area Indoor Organic Photovoltaic Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Luke et al investigated the low light IOPVs device performance of commercially feasible inverted device architecture, employing all solution processed R2R fabrication technique and relatively low-cost polymer (P3HT) donor and NFA (O-IDTBR) acceptor as active layer materials. [104] This is particularly important as thick layers are easier to manufacture by R2R processes (Figure 9a). Their results suggested that screening of possible low light OPV devices using 1 sun illumination is not appropriate, as some OPV devices that perform well at low light intensities may appear to not work well under standard illumination conditions.…”
Section: Large-area Indoor Organic Photovoltaic Modulesmentioning
confidence: 99%
“…Although, such interfacial reaction mechanisms can be stopped through effective passivation of metal ion doping or interfacial modification, the development of suitable interlayers with excellent performance and stability are prerequisite for the progress of high-performance and stable OPV devices. [104,114,115] Cui et al demonstrated the device stability of PBDB-TF:IO-4Cl based conventional OPV cell under continuous indoor light illumination (Figure 10a,b). [2] The OPV cells maintained their initial PCE after 1000 h that exhibits a great potential of OPVs for indoor applications with excellent device performance and operational stability.…”
Section: Device Stability Of Indoor Organic Photovoltaicsmentioning
confidence: 99%
“…Unfortunately, most publications lack in absolute data and only provide the relative spectral irradiance of their LED, [14,15,17,21,25,26,33,63] which is much easier to obtain, in some cases not even relative light source spectra are given. [24,34,64] Hence, in many publications the illuminance is determined by a lux meter [15,16,21,25,29,30,32] and then the input power density is calculated with the measured illuminance and the relative spectra of the light source. The lux meter, however, only really measures relative photon densities and converts those to irradiance values using an assumption about the spectral shape of the light source.…”
Section: Determination Of Input Power Densities At Constant Illuminancementioning
confidence: 99%
“…Although efficiencies for indoor organic photovoltaics (iOPV) [ 14–35 ] and other emerging indoor photovoltaics (iPV) technologies such as halide perovskites [ 36–43 ] or dye‐sensitized solar cells [ 44–50 ] have improved substantially, it is hard to quantify progress and determine champion solar cells due to a lack of standardized comparison methods. [ 12,51,52 ] Different authors use different conditions to evaluate the performance of their devices.…”
Section: Introductionmentioning
confidence: 99%
“…To realize wireless and battery-free self-powered sensor nodes for practical applications, IPV is an attractive option because it harvests light energy from ambient conditions and generates electricity with high power output. Among the various IPV technologies, organic photovoltaic is most suitable because of its advantages of solution processing, flexibility, and the adjustable absorption spectra ( Song et al., 2020 ; Zhu et al., 2021 ; Luke et al., 2021 ; Ma et al., 2021b ; Cui et al., 2020a ). In the past several years, great progress has been made in organic IPV.…”
Section: Introductionmentioning
confidence: 99%